Peran Manajemen Risiko dan Pengendalian Internal dalam Meningkatkan Kinerja Karyawan di Bank BJB Syariah KCP Majalaya - Cucun Sumiati; Nur'aeni Nur'aeni (Jurnal Dimamu, 2022)
This study aims to determine how the role of risk management and internal control in improving employee performance at Bank BJB Syariah KCP Majalaya. The object of research in this report is to describe the level of performance of employees at Bank BJB Syariah KCP Majalaya. The type of research is descriptive qualitative with primary data types and uses data collection techniques in the form of observation, interviews, documentation, literature study. The population is all 12 employees at Bank BJB Syariah KCP Majalaya.The results showed that Bank BJB Syariah KCP Majalaya has implemented the principles of risk management, namely: Transparency, Accountability, Responsibility, Professional, Fairness so that it can boost employee performance levels. The existence of the Sharia Supervisory Board also encourages a level of discipline in fulfilling sharia principles in raising funds, channeling funds, and providing services. Forming a Risk Management Committee (KMR), a Risk Management Work Unit (SKMR) that is independent of the Operational Work Unit both structurally and operationally as a means to support the smooth implementation of Risk Management at the Bank. Implementation of compliance, Internal Audit and Internal Audit functions to ensure the Bank's compliance with applicable regulations that can boost employee performance levels to comply with / implement commitments made by the bank to the Financial Services Authority.